Women of the European Union : the politics of work and daily life - Garcia-Ramon,Maria Dolors (Editor) (International studies of women and place, 1996)
Women of the European Union challenges gender-blind assessments of the economic and social aspects of EU policies to examine the real implications of union for the diversity of women in the member states. The authors also analyse how women's work and daily lives are shaped by local and national policies, by local and global economic conditions, and by diverse and changing cultural values.